A Case of Olfactory Neuroblastoma Developing Bilateral Retropharyngeal Lymph Node Metastasis 14-years After Skull Base Surgery - Mizumoto, Marie; Furukawa, Tatsuya; Yui, Mitsuko; Iritani, Keisuke; Tatehara, Shun; Inokuchi, Go; Teshima, Masanori; Shinomiya, Hirotaka; Kimura, Hidehito; Kiyota, Naomi; Sasaki, Ryohei; Nibu, Ken-Ichi (Kobe journal of the medical sciences, 2024)
Olfactory neuroblastoma (ONB) is an uncommon malignant tumor and is usually treated by a multidisciplinary approach includes surgery, radiotherapy, and chemotherapy. A 62 years-old male had a tumor in the nasal cavity and diagnosed as ONB with Kadish A stage. Anterior skull base surgery was performed as radical treatment. Since the surgical margin was negative, no postoperative radiotherapy was administered. 14 years after the surgery, bilateral otitis media with effusion (OME) was occurred, we found the recurrence tumor at bilateral retropharyngeal lymph node (RPLN) which surrounded the internal carotid arteries. Since these were unresectable, we planned chemoradiotherapy which was 70Gy of intensity modulated radiotherapy combined with two courses of carboplatin and etoposide. The tumor volume was reduced and bilateral OME were improved. He has been alive for 3 years after salvage treatment. Although ONB has a relatively good prognosis, it is known to often cause cervical lymph node metastasis. Grades III and IV of Hyams classification are considered high risk. This case, initial tumor was limited in the nasal cavity and its clinical classification was early stage, but Hyams classification was grade III. In reference to this case, considering that RPLN metastasis are difficult to radically resect at the salvage surgery, including this area in postoperative radiotherapy was considered an option.